A Fatal Case of Necrotizing Fasciitis Caused by a Highly Virulent Escherichia coli Strain - Sadjia Bekal; André Vincent; Alex Lin; Josée Harel; Jean-Charles Côté; Cécile Tremblay (Canadian Journal of Infectious Diseases and Medical Microbiology)
Necrotizing fasciitis is a serious disease characterized by the necrosis of the subcutaneous tissues and fascia. E. coli as the etiologic agent of necrotizing fasciitis is a rare occurrence. A 66-year-old woman underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy. She rapidly developed necrotizing fasciitis which led to her death 68 hours following surgery. An E. coli strain was isolated from blood and fascia cultures. DNA microarray revealed the presence of 20 virulence genes.